Sistema de controle interno no anteprojeto de lei orgânica da administração pública federal: percepção dos servidores da Controladoria-Regional da União no Estado de Pernambuco - Lima Neto, Ruitá Leite (2012)
This research’s goal was to identify the perception of civil servants from the Office of the Comptroller General in Pernambuco State about the contributions of the Federal Public Administration Organic Draft Law to strengthen the internal control system of the Brazilian Federal Executive Branch, especially in the matters of 'time of the audit' and 'type of the audit'. To this end, questionnaires were applied, filled by 92% of public employees interviewed. It concluded that, for these servers, the internal control system profile proposed by the Draft Law, called 'Post-audit-Performance' by this study, is not the most appropriated. With respect to 'type of the audit', there was convergence between the Draft Law propositions and civil servants opinions in the defense of the performance audit, without neglecting the legality audit. However, when it comes to 'time of the audit', while the lawyers argue for a predominant role of post-audit, public officials agreed that Internal Audit should have an effective planning, able to set the proper time for action in each case. Finally, as a contribution to the debates, this study has built proposals of guidelines for governmental control that could be incorporated into the Organic Law. These proposals are: (i) time of the audit defined based on careful planning and (ii) focus on verifying compliance with the public interest.